Trade union merger in Singapore. - Toh, Ying Lei. (2011)
The topic of union mergers has been studied by many researchers. Although these studies help us to gain better understanding of union mergers, their application to Singapore may be limited, due to Singapore’s unique industrial relations landscape. This paper explores the union merger process in Singapore by analysing a recent merger using the Chaison Trade Union Merger Model (Chaison, 1986). Information about the merger is gathered through interviews with parties involved. Building on the case study, the paper further examines the role of a labour federation in its affiliates’ merger, distinguishing between macro-focused and micro-focused labour federations. The paper also highlights the important lessons that can be drawn from the merger experience and discusses the possible difficulties in applying them to other countries.